An Act for Establishing a Militia Within this State, § 6, 1782 Jan. Adjourned Sess. of Del. Acts 1, 3 - (:unkn) unknown (General Publisher, 1782)
Required every person aged eighteen to fifty to provide a musket or firelock with a bayonet, a cartouch box with twenty-three cartridges, priming wire, a brush, and six flints all in good order. Also required providing the same from parents who are tax rated at eighteen pounds, or apprentices. Violators fined at twenty-shillings for ever two months neglect or default.
--
Keywords: REQUIRED POSSESSION